2020
DOI: 10.1080/1120009x.2020.1775424
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir/ritonavir as a third agent in the antiviral regimen for SARS-CoV-2 infection

Abstract: Corona Virus Disease (CoVID-19) is an emerging public health problem rapidly spread globally. New treatment options for patients with severe symptoms and ways of reducing transmission in the community are taken into consideration. A retrospective study was conducted in the Department of Infectious Diseases of Alexandroupolis (Greece) including 16 patients with CoVID-19. They were classified into two groups, A and B. Group A received lopinavir/ritonavir as a third agent in the antiviral regimen, while group B d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Indeed, in our patients, consistent with the recent reports [23], lymphopenia was more observed in Group S than Group M. In addition, the comorbid lipid disorders were more prevalent in Group S patients, which might be associated with abnormal inflammatory processes caused by deteriorated lipid metabolisms [24,25]. Although there was no clear evidence to treat SARS-CoV-2 infection hydroxychloroquine / chloroquine [14], ivermectin [26], lopinavir / ritonavir [27], and anti-interleukin agents were reported to be potentially effective [11]. Since thrombotic disorders were also reported as one of the critical manifestations [28,29], we used various combinations of drugs and anticoagulant therapies in Group S patients (Table 3).…”
Section: Treatments and Clinical Outcomessupporting
confidence: 90%
“…Indeed, in our patients, consistent with the recent reports [23], lymphopenia was more observed in Group S than Group M. In addition, the comorbid lipid disorders were more prevalent in Group S patients, which might be associated with abnormal inflammatory processes caused by deteriorated lipid metabolisms [24,25]. Although there was no clear evidence to treat SARS-CoV-2 infection hydroxychloroquine / chloroquine [14], ivermectin [26], lopinavir / ritonavir [27], and anti-interleukin agents were reported to be potentially effective [11]. Since thrombotic disorders were also reported as one of the critical manifestations [28,29], we used various combinations of drugs and anticoagulant therapies in Group S patients (Table 3).…”
Section: Treatments and Clinical Outcomessupporting
confidence: 90%
“…Several recent studies have identified promising antiviral drug candidates that might be effective against SARS-CoV-2 infection by inhibiting some aspects of COVID-19 ( Table 1 ). These include atazanavir [43] , favipiravir [44] , IFN-α2b (interferon) [45] , lopinavir-ritonavir [46] , remdesivir [47] , ribavirin [48] , and umifenovir [49] ( Table 1 ). A number of in silico, preclinical or clinical studies have suggested that these drugs could have favorable clinical outcomes for SARS-CoV-2 patients [50] , reducing virus load, and mitigating the “cytokine storm”.…”
Section: Drug Repurposing For Covid-19 and Affected Cytokinesmentioning
confidence: 99%
“…Forty-four studies were excluded based upon screening of abstract, and a further 16 were excluded since they did not include individuals with SARS-CoV-2, or were an in vitro studies. A total of 98 studies including nine randomized studies (RCTs) ( Beigel et al, 2020 ; Cao et al, 2020 ; Chen C. et al, 2020 ; Goldman et al, 2020 ; Hung et al, 2020 ; Li et al, 2020 ; Lou et al, 2020 ; Wang Y. et al, 2020 ; Zheng et al, 2020 b) and 29 non-randomized studies ( Antinori et al, 2020 ; Cai et al, 2020 ; Chen W. et al, 2020 ; Chen H. et al, 2020 ; Deng et al, 2020 ; Gautret et al, 2020 ; Giacomelli et al, 2020 ; Grein et al, 2020 ; Haerter et al, 2020 ; Holshue et al, 2020 ; Kim et al, 2020 ; Lian et al, 2020 ; Lim et al, 2020 ; Liu et al, 2020 ; Panagopoulos et al, 2020 ; Shi et al, 2020 ; Vizcarra et al, 2020 ; Wang Z. et al, 2020 ; Xi et al, 2020 ; Xu et al, 2020 ; Yan et al, 2020 ; Yang et al, 2020 ; Ye et al, 2020 ; Young et al, 2020 ; Zhang et al, 2020 ; Zheng et al, 2020 a; Zhou et al, 2020 b; Zhu et al, 2020 b; Zuo et al, 2020 ) examining the use of antivirals in COVID-19 were included ( Figure 1 ). We also included another 60 registered clinical trials which were at clinical phases 2, 3, or 4 ( Supplementary Appendix Table 1 , Supplementary Appendix Figure 1 , and Supplementary Appendix Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%